Development of AJARKO Learning Media (Computer Network Application) Based on Android in The Information Technology Education Study Program: Pengembangan Media Pembelajaran AJARKO (Aplikasi Jaringan Komputer) Berbasis Android Pada Prodi Pendidikan Teknologi Informasi - Septyanto, Fachryzal; Hasanah, Fitria Nur (Indonesian Journal of Education Methods Development, 2022)
The purpose of this study was to find out how the development of AJARKO learning media (computer network application) based on Android in the information technology education study program and to determine the feasibility of the developed media. The media was developed using Adobe Flash Professional CS6 software. The type of research used is R&D using the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. The research subjects were 4th semester PTI students. The validation results obtained from media experts amounted to 89.3% which was declared very feasible. Then from the material and question experts each got a score of 67.6% and 67.5% which were declared eligible. The assessment of the respondents got an average value of 88.4% which was declared very feasible. It is concluded that this android-based computer network learning media is feasible to be applied to the learning process.